2022
DOI: 10.1177/13591045221105194
|View full text |Cite
|
Sign up to set email alerts
|

Sluggish cognitive tempo, eating habits, and daytime sleepiness in obese adolescents

Abstract: Objective Rates of obesity have risen steeply in the western world in all age groups. Sluggish Cognitive Tempo (SCT) is characterized by a cluster of symptoms. Daytime sleepiness, commonly seen in obesity, may share a similar origin with sleepiness and daydreaming symptoms of SCT. This study aims to investigate the relationship between obesity, SCT, daytime sleepiness, and eating habits. Method Adolescents, aged between 10–17 years, with a BMI >95th centile, were recruited to the study. Clinical interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(70 reference statements)
1
0
0
Order By: Relevance
“…This study added additional evidence to these association among Turkish youth, and identified a moderate and positive relationship between SCT scores and ADHD RS-IV-IN scores. Although SCT was more strongly correlated with the inattentive type, a weak and positive relationship was found with hyperactive-impulsive type ADHD, and is similar to that reported among adults (Fredrick et al, 2021) and youth with obesity (Öğütlü et al, 2022).…”
Section: Discussionsupporting
confidence: 83%
“…This study added additional evidence to these association among Turkish youth, and identified a moderate and positive relationship between SCT scores and ADHD RS-IV-IN scores. Although SCT was more strongly correlated with the inattentive type, a weak and positive relationship was found with hyperactive-impulsive type ADHD, and is similar to that reported among adults (Fredrick et al, 2021) and youth with obesity (Öğütlü et al, 2022).…”
Section: Discussionsupporting
confidence: 83%